Review of O. V. Sokolovskaia’s Grecheskaia koroleva Ol’ga Konstantinovna – Pod molotom sud’by [The Greek queen Olga Konstantinovna: under the hammer of fate] - Frary, Lucien James (Historein, 2014)
OV Sokolovskaia, Grecheskaia koroleva Ol’ga Konstantinovna – Pod molotom sud’by [The Greek queen Olga Konstantinovna: under the hammer of fate], Moscow: Institute of Slavic Studies, 2011. 212 pp.